Characterization of the Japanese Management Technique 5S. Polytechnic Dining Room Case - M. Izurieta; G. Miño; D. Vallejo (ESPOCH Congresses)
This research aimed to characterize the Japanese 5S management technique, using a case study of the Polytechnic Dining Room, given that in this unit you can apply the 5S technique without any problem, and improve quality, productivity and competitiveness. Several elements were examined including the existence of work material, procedures for eliminating unnecessary materials, location of work materials, cleaning of work areas, standardization of processes, use of uniforms, and protective equipment, among others. Qualitative and quantitative approaches were used. A documentary research instrument was applied, using a Likert scale with ordinal variables. According to the results, those that obtained the highest rating of 7 were as follows: Seiris (classification) 25%, Seiton (Order) 36%, Seiso (Cleaning) 32%, Seiketsu (Standardization) 36%, and Shitsuke (Maintenance) 57%. Therefore, we conclude that in Shitsuke there was greater employee commitment, and Seiri obtained the lowest qualification.